2018
DOI: 10.3892/mco.2018.1615
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss during neoadjuvant/adjuvant chemotherapy for�early stage breast cancer: A retrospective cohort study

Abstract: The present study aimed to evaluate the extent of loss in bone mineral density (BMD) during neoadjuvant and adjuvant chemotherapy for early stage breast cancer. A retrospective cohort study was conducted to quantify the loss of BMD one year following the start of chemotherapy and to identify potential risk factors of excessive BMD loss. Based on DXA-scans prior to and one year following chemotherapy, the loss of BMD was evaluated in early stage breast cancer patients treated from January 2012 to December 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…This beneficial effect could be due to the activation of AMPK, which has a potential therapeutic target for osteoarthritis 72 . Besides, even though chemotherapeutics are associated with a significant loss in bone mineral density of BC patients 73 ; fortunately, metformin improves the quality of bones and reduces fracture risk. A potential reason for this effect is the key role of AMPK in signaling pathways involved in bone physiology 74 .…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial effect could be due to the activation of AMPK, which has a potential therapeutic target for osteoarthritis 72 . Besides, even though chemotherapeutics are associated with a significant loss in bone mineral density of BC patients 73 ; fortunately, metformin improves the quality of bones and reduces fracture risk. A potential reason for this effect is the key role of AMPK in signaling pathways involved in bone physiology 74 .…”
Section: Discussionmentioning
confidence: 99%
“…This increase of bone density has been suggested to be a result of the rise in physical burden due to the high center of gravity [ 8 ]. In a study by Axelsen et al [ 24 ], it was concluded that chemotherapy in breast cancer patients results in a significant bone mineral densitometry (BMD) loss due to an increase in bone turnover, leading to osteoporosis. Furthermore, Huang et al [ 25 ] also found that both the SUV mean and SUV max in osteoporotic patients are significantly lower compared with those in non-osteoporotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…(44) Chemotherapy can also cause loss of bone, which increases fracture risk, especially in older populations. (45,46) Bisphosphonate drugs such as ZA and denosumab prevent bone loss and fractures in patients with bone-wasting disorders. (47,48) Patients with bone metastases or treated with certain chemotherapies are also treated with denosumab or a bisphosphonate to prevent bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy treatment is effective at combating tumor cell growth and proliferation, but an array of chemotherapy drugs cause loss of muscle mass and muscle weakness, which reduces a patient's quality of life . Chemotherapy can also cause loss of bone, which increases fracture risk, especially in older populations . Bisphosphonate drugs such as ZA and denosumab prevent bone loss and fractures in patients with bone‐wasting disorders .…”
Section: Discussionmentioning
confidence: 99%